Visual Word Recognition in Reading Kannada - Jayashree C Shanbal; Prema K.S. (Journal of All India Institute of Speech and Hearing, 2007)
Reading is a complex cognitive process. It is a process that requires co-ordination of a series of sub-functions, which include visual functions, verbal functions and other cognitive functions like memory and attention. Impairment in any one or more of these functions can affect reading. Amongst a host of reading processes, visual word-recognition in children is widely investigated. There are many models proposed to explain visual-word recognition. The most widely discussed model is the ‘Dual route cascaded (DRC) model(Coltheart, Rastle, Perry, Langdon & Ziegler, 2001). The purpose of the present study is to explore visualword recognition in Kannada in children with normal reading abilities. Further, the study also investigated if lexical processing in reading Kannada is through serial or parallel processing. The subjects consisted of 10 children in the age range of 10-12 years with normal reading ability. Children witht a minimum of four years of exposure to Kannada reading were selected. Basic reading level in Kannada was established using theKannada Reading Test developed by Purushothama (1992). The children were required to identify the word in a given word-nonword pair presented through DMDX software program. The reaction time of their responses to identify the word in a given word-nonword pair was measured and recorded with the help of the DMDX software. The results of the study are discussed in light of the existing literature on ‘Dual route cascaded (DRC) model’.